TRANSPARENCY AND CONFIDENTIALITY REQUIREMENTS IN INVESTMENT TREATY ARBITRATION - Azhaham Perumal Perumal Saravanan; Subramanian Ramamurthy Subramanian (BRICS Law Journal, 2018)
he values of confidentiality and transparency are often invoked in the theory and practice of investment treaty arbitration. Transparency is considered to be one of the key aspects of good governance and corporate social responsibility. It includes the obligation of the host state to publish all the legal rules, regulations and other statutory requirements affecting investors. Confidentiality is considered the hallmark and unique feature of arbitration as a dispute resolution mechanism. However, it is difficult to balance these two values, in principle due to the difference in the various investment arbitration cases, as well as the high degree of public interest involved in such proceedings. The competing interests between transparency and confidentiality have significantly increased in the recent past, and the difficulty lies in drawing a medial line between them. There is also debate as to what extent non-disputing parties are allowed to participate in investment arbitration, and what the essential requirements are to admit them.It is in this connection that this article makes an in-depth analysis of how investment arbitration frameworks have approached the questions of transparency, confidentiality and amicus curiae participation over the years. The article assesses and explores similar issues within the International Convention on the settlement of investment disputes between States and nationals of other States, 1965 (ICSID), the North American Free Trade Agreement, 1994 (NAFTA) and the United Nations Commission on International Trade Law (UNCITRAL) Arbitration Rules, 1978. The study also makes a critical analysis of celebrated cases falling within each category. The article further elaborates the transparency requirements in the U.S. Model Bilateral Investment Treaty (BIT), 2012, and the recently adopted Indian Model BIT, 2015. The study is very significant because the United Nations has recently adopted the Convention on Transparency in Treaty-based InvestorState Arbitration, 2014 (Mauritius Convention), which ensures transparency and public accessibility to investor-state arbitration.